2021
DOI: 10.3390/ijerph182111093
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intention to Participate in Breast Cancer Screening among Urban Chinese Women: An Application of the Protection Motivation Theory

Abstract: Despite the significance of early detection of breast cancer through screening, the screening uptake in China remains relatively low. Protection motivation theory (PMT) suggested by Rogers is one of the theories concerning threat appeal. This study aimed to apply the protection motivation theory (PMT) in predicting breast cancer screening intention. In this cross-sectional study, a sample of Chinese urban women was recruited using the convenient sampling method from five communities in Wuhan. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…As opposed to other studies with a sole outcome variable, this study subdivided the outcome variable into behavioral intentions and behaviors. The results of this study also extend previous studies on cervical cancer screening and breast cancer screening conducted in China (Bai Y et al, 2018c;Zhang M et al, 2021b). This study showed that health education had a direct and most signi cant effect on cognitive severity and self-e cacy, screening knowledge on self-e cacy, technical service support, environmental improvement, and self-e cacy on behavioral intentions, and social support and fear arousal on behaviors.…”
Section: 5multigroup Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…As opposed to other studies with a sole outcome variable, this study subdivided the outcome variable into behavioral intentions and behaviors. The results of this study also extend previous studies on cervical cancer screening and breast cancer screening conducted in China (Bai Y et al, 2018c;Zhang M et al, 2021b). This study showed that health education had a direct and most signi cant effect on cognitive severity and self-e cacy, screening knowledge on self-e cacy, technical service support, environmental improvement, and self-e cacy on behavioral intentions, and social support and fear arousal on behaviors.…”
Section: 5multigroup Analysissupporting
confidence: 88%
“…The protective motivation theory suggests that an individual's ultimate health behaviors are determined by a combination of external objective environmental factors and internal subjective personal factors. Many studies have used the protective motivation theory to explain the motivation of health behaviors in populations, mainly in screening behaviors for colorectal, skin, cervical, and breast cancers (Bai Y et al, 2018;Roozbahani N et al, 2020;Wei W et al, 2022;Zhang M et al, 2021b). Previous studies have shown that rural residents have signi cantly lower uptake of cancer screening for colorectal, cervical, and breast cancers relative to urban residents, which may lead to poorer survival (Walji LT et al, 2021).…”
mentioning
confidence: 99%
“…Breast self-awareness and preventive self-regulation behaviors such as lifestyle, nutrition, and physical activity were introduced to the participants, and they understood and internalized the benefits of these solutions which led to the promotion of their self-efficacy. Zhang et al aimed to determine the determinants of the intention of breast cancer screening behaviors in Chinese women based on the PMT, and their findings showed that self-efficacy is directly related to the intention of mammography behavior (42). Rezaeian et al conducted a study to determine the effect of an educational program based on the Health Belief Model on the knowledge and health beliefs of 290 women aged 40 and over about breast cancer and mammography in Isfahan and reported a statistically significant difference (P > 0.05) in the mean scores of the constructs of perceived sensitivity, perceived severity, perceived benefits and barriers, self-efficacy, and motivation of women in the test group compared to women in the control group after the educational intervention (43).…”
Section: Discussionmentioning
confidence: 99%
“…They also recommended that healthcare providers develop educational programs based on PMT to enhance BC screening behaviors. Zhang et al (2021) examined BC screening intention based on PMT among Chinese adult females. They confirmed the significant role of PMT in BC screening by using structural equation modeling.…”
Section: Discussionmentioning
confidence: 99%